Wave breaking for periodic solutions of a nonlinear shallow water equation. Issue 2 (22nd January 2022) - Basu, Biswajit; Haziot, Susanna V.; Staino, Andrea
ABSTRACT: We consider a nonlinear shallow water equation. An inequality condition for wave breaking has been established for the Cauchy problem with periodic domain. Numerical computation confirms the result, as breaking happens for waves with a chosen initial profile satisfying the theoretical condition for wave breaking.